2012
DOI: 10.1159/000339591
|View full text |Cite
|
Sign up to set email alerts
|

Differential Distribution of CYP2A6 and CYP2A13 in the Human Respiratory Tract

Abstract: Background: Human CYP2A6 and CYP2A13 play important roles in metabolic activation of many pulmonary carcinogens and thus their expression and distribution may determine the pulmonary susceptibility to metabolically activated carcinogens and the following lung cancer development. Because of the 93.5% of amino acid identity between CYP2A6 and CYP2A13, generation of antibodies specific to CYP2A6 or CYP2A13 has limited immunohistochemical (IHC) analysis of CYP2A6 and CYP2A13 levels in the respiratory tract. Object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 67 publications
3
20
0
Order By: Relevance
“…15 However, Zhu et al 16 used an anti-P450 2A13 antibody and reported immunostaining in trachea and bronchiole but not alveolar cells. The difference in the bronchiole data of Chiang et al 15 are not understood at this time. The P450 2A13 proximal promoter has been reported to interact with members pf the CCAAT/enhancer binding protein (C/EBP) family in the respiratory tract, and silencing by epigentic mechasnisms has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…15 However, Zhu et al 16 used an anti-P450 2A13 antibody and reported immunostaining in trachea and bronchiole but not alveolar cells. The difference in the bronchiole data of Chiang et al 15 are not understood at this time. The P450 2A13 proximal promoter has been reported to interact with members pf the CCAAT/enhancer binding protein (C/EBP) family in the respiratory tract, and silencing by epigentic mechasnisms has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…coumarin and phenacetin, and also metabolic activation of tobacco-related nitrosamines (including NNK and NNN) to carcinogenic metabolites (140,141). However, CYP2A13 is shown to be more active than CYP2A6 in activating NNK and NNN (140,141) and these findings are of interest because the latter enzyme is mainly expressed in respiratory organs, the sites of exposure to numerous environmental chemicals including NNK, NNN, and PAHs (4,138,139). As described above, several chemicals that inhibit CYP2A13 and 2A6 enzymes suppress tumor formation caused by NNK, 7,12-DMBA, B[ a ]P, and azoxymethane (Table 3) (4751), it is interesting to examine whether various xenobiotic chemicals interact with and inhibit CYP2A13 and 2A6-dependent catalytic activities and are metabolized by these P450 enzymes (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK), N -nitrosonornicotine) and to metabolize different kinds of chemicals including coumarin, nicotine, phenacetin, naphthalene, 4-aminobiphenyl, and styrene (Su et al, 2000; Chiang et al, 2011; Fukami et al, 2008; Wong et al, 2005a; Wong et al, 2005b). P450 2A13 is mainly expressed in the respiratory tract and P450 2A6 is primarily found in the liver (Su et al, 2000; Chiang et al, 2012; Zhu et al, 2006). Recent studies have shown that P450 2A13 is more active than P450 2A6 in activating NNK, N -nitrosonornicotine, and other environmental carcinogens that cause cancer in the respiratory organs (Wong et al, 2005a; Wong et al, 2005b; Chiang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%